Fear Of Crime And Perceived Risk Of Victimization Among College Students - Truman, Jennifer (2007)
Fear of crime is argued to be a social problem that may lead to restriction of activities, increased security costs, and avoidance behaviors. Findings from research indicate that there are many demographic influences on the fear of crime. Specifically, gender has been found to be one of the most consistent predictors of crime, that is, females significantly fear crime more than males. Additionally, research suggests that a person's fear of crime or perceived risk to crime may increase their engagement in precautionary behaviors, such as carrying a weapon for protection. The current study examined these relationships using data collected from 588 students at the University of Central Florida in the fall of 2006. The results indicated that females reported significantly higher mean scores on the fear scale for all crimes except property crimes, as well as higher mean scores for most crimes on the perceived risk of victimization scale. Females also reported feeling less safe from crime in their neighborhood and at home. Furthermore, females were more likely to engage in precautionary behaviors, but less likely to engage in risky behaviors. Fear of crime was not a significant predictor of the use of precautionary behaviors. However, respondents with greater perceived risk were more likely to use a greater number of precautionary behaviors. Additionally, respondents who had a perceived lack of safety were more likely to use precautionary behaviors and engage in them more often. Risky lifestyle behaviors were not significant predictors of either fear or guardianship activities. Exposure to the media was only shown to increase fear, perceived risk, and perceived lack of safety at the bivariate level. And finally previous victimization was not a significant predictor of fear or perceived risk. Overall, the results were fairly consistent with previous literature. Implications for future research and policy are discussed